2021
DOI: 10.1016/j.celrep.2021.110110
|View full text |Cite
|
Sign up to set email alerts
|

YTHDC2 is essential for pachytene progression and prevents aberrant microtubule-driven telomere clustering in male meiosis

Abstract: Highlights d YTHDC2 is required for meiotic progression through the pachytene stage d YTHDC2 deficiency causes a massively dysregulated transcriptome in pachytene cells d Altered transcripts in YTHDC2-deficient cells encode microtubule network proteins

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 73 publications
5
29
0
Order By: Relevance
“…As well as a postulated role in the mitosis-meiosis switch, Ythdc2 has recently been suggested to have a later role at pachytene of meiosis 1, and this is also suggested by our data ( 49 ). A male Ythdc2 mouse model deficient for YTHDC2 at pachytene demonstrated aberrant microtubule network changes and telomere clustering with germ cell apoptosis ( 49 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As well as a postulated role in the mitosis-meiosis switch, Ythdc2 has recently been suggested to have a later role at pachytene of meiosis 1, and this is also suggested by our data ( 49 ). A male Ythdc2 mouse model deficient for YTHDC2 at pachytene demonstrated aberrant microtubule network changes and telomere clustering with germ cell apoptosis ( 49 ).…”
Section: Discussionsupporting
confidence: 88%
“…As well as a postulated role in the mitosis-meiosis switch, Ythdc2 has recently been suggested to have a later role at pachytene of meiosis 1, and this is also suggested by our data ( 49 ). A male Ythdc2 mouse model deficient for YTHDC2 at pachytene demonstrated aberrant microtubule network changes and telomere clustering with germ cell apoptosis ( 49 ). Here, we gained further insight into the role of YTHDC2 in the developing human ovary from cluster and pathway enrichment analyses of differentially expressed genes between early- and late-stage ovaries throughout human prophase 1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We unexpectedly observed that germ cells lacking YTHDC2 helicase activity arrested during meiotic prophase, days after meiotic entry. This result is likely attributable to loss of a later function of YTHDC2 during meiosis, supported by a recent study that conditionally deleted Ythdc2 after meiotic entry during spermatogenesis and indicated a role for YTHDC2 during mid-meiotic prophase (Liu et al 2021). Our helicase-dead allele showed a meiotic arrest phenotype similar to that described for the conditional Ythdc2 allele.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively, Jain et al (2018) suggested that YTHDC2 interacts with proteins that have known roles in nonsense-mediated mRNA decay such as XRN1, UPF1 and MOV10 rather than with MEIOC to destabilize its target transcripts. In addition, YTHDC2 regulates pachytene by maintaining meiotic transcriptome and preventing microtubule network changes that may lead to telomere aggregation in male meiosis ( Liu et al, 2021 ). Therefore, YTHDC2 as a protein with multiple domains, has complex functions related to the regulation of translation efficiency and transcriptional stability.…”
Section: The Role Of M 6 a In Spermatogenesismentioning
confidence: 99%